Factors that Influence Student Discipline at Saengarun Anusorn School Narathiwat Thailand - Heriantini, Dian; Mubin, Ali; Harahap, Erpin (PT FORMOSA CENDEKIA GLOBAL, 2024)
Discipline is an inseparable part of the goals of education itself, so that discipline becomes the main element driving education in the realm of student character formation, so that discipline becomes the main element driving education in the realm of student character formation. In this journal, the author will discuss several factors that influence student discipline in elementary schools, namely Saengarun Anusorn, located in Narathiwat Province, Southern Thailand. Apart from being a benchmark for cultural differences between Indonesia and Thailand, this journal will also share the author's experiences while teaching at the Saengarun Anusorn elementary school. Hopefully this journal will be an inspiration and source of motivation about how a teacher should be able to foster a sense of discipline in students at the elementary school level, both at home and abroad.